Ibn Qutaybah's contribution to Qur'anic exegesis an analytical study of his work ta'wil mushkil al Qur'an (the interpretation of the difficult Passages of the Qur'an) - Muhammad Amin Abdul_Samad (Fajar Copy Paste, 2018)
st,1./ws.c.1